Unusual presentation of multiple ingested magnets in a 12-year-old boy: A case report - Ashley Ramirez; Yi-Horng Lee; Vasantha Kondamudi; Francisca Velcek (Journal of Pediatric Surgery Case Reports)
Introduction: Magnetic foreign body ingestions were previously quite rare, but as newer and stronger magnets become more commonly incorporated into daily lives, ingestions are becoming more frequent. This case involves an unlikely patient with a deceiving presentation which obscured the severity of his jejunal perforation. Case: This is a 12-year-old boy with no past medical history who presented with non-peritonitic, mild abdominal pain. Vital signs and laboratory testing were all within normal limits. Patient did not disclose a history of foreign body ingestion when he first presented. His initial physical exam was significant for mild left sided abdominal tenderness without any peritoneal signs. He was evaluated with a CT scan of the abdomen and pelvis, and to everyone's surprise, there was a string of round metallic objects present, resembling magnetic beads. Only at that time did the patient admit to ingesting magnetic beads that were purchased for his younger sister as a toy. He never disclosed the timing of the ingestion or the circumstance in which he ingested them. The CT scan did not demonstrate any free air or inflammation around the bowel loops that contained these beads. Since his abdominal exam was relatively benign and the CT scan did not reveal any concerning findings, we elect to obtain an abdominal X-ray at that time as a baseline with the plan to follow serial abdominal X-rays to track the progression of these beads throughout the GI tract. A repeat abdominal X-ray 6 hours later did not show any progression of the ingested beads, and his abdominal pain became more intense during the time of our observation. This prompted operative intervention via exploratory laparotomy. A periumbilical midline incision was made and the bowel loops were inspected. Intraoperatively, we observed that the magnetic beads have perforated through the jejunal wall with serosal inflammation of the adjacent bowel loop. We did not see any fistula between any bowel loops. Repair was accomplished via resecting the small bowel segment containing the perforation and primary anastomosis. The inflamed serosal layer at the adjacent loop was plicated with a series of Lembert sutures. The patient recovered well without complications. He was discharged to home on the fifth postoperative day, and he remained well when he returned for follow up three months later. Conclusion: A low threshold for surgical intervention should be maintained for children presenting with multiple magnet ingestion that is visualized on imaging. This is true especially in the setting of worsening pain and evidence of abdominal tenderness even when there is no free air seen on imaging studies.